2009
DOI: 10.4049/jimmunol.0802972
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific Suppression of Inflammatory Arthritis Using Liposomes

Abstract: Existing therapies for rheumatoid arthritis and other autoimmune diseases are not Ag specific, which increases the likelihood of systemic toxicity. We show that egg phosphatidylcholine liposomes loaded with Ag (OVA or methylated BSA) and a lipophilic NF-κB inhibitor (curcumin, quercetin, or Bay11-7082) suppress preexisting immune responses in an Ag-specific manner. We injected loaded liposomes into mice primed with Ag or into mice suffering from Ag-induced inflammatory arthritis. The liposomes targeted APCs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 39 publications
1
85
0
1
Order By: Relevance
“…It helps in decreasing the build-up in size of liposomal vesicles after lyophilzation [Capini et al 2009]. Since it also acts as a non-penetrating cryoprotectant during semen cryopreservation and thawing [Critser et al 1988], its presence in LFM was found to be beneficial for preventing loss of sperm function during the freeze-thaw process.…”
Section: Discussionmentioning
confidence: 99%
“…It helps in decreasing the build-up in size of liposomal vesicles after lyophilzation [Capini et al 2009]. Since it also acts as a non-penetrating cryoprotectant during semen cryopreservation and thawing [Critser et al 1988], its presence in LFM was found to be beneficial for preventing loss of sperm function during the freeze-thaw process.…”
Section: Discussionmentioning
confidence: 99%
“…This includes presentation of small amounts of antigen by sub-optimally activated DC, presentation by DC lacking costimulatory or expressing suppressive molecules, or presentation by specialized lamina propria DC expressing retinal dehydrogenase that catalyses the conversion of retinal to retinoic acid [34][35][36][37]. When we rendered myeloid DC RelB-deficient and transferred them into wild-type hosts with inflammatory arthritis, or delivered mice arthritogenic antigen packaged with an inhibitor that suppressed RelB, targeted DC induced antigen-specific FoxP3+ T regulatory cells [38,39]. Similar effects occurred upon transfer of antigen-loaded DC that had been transfected with RelB siRNA [40].…”
Section: Self-tolerance and Its Regulationmentioning
confidence: 98%
“…Currently, RA treatment is focused on easing the symptoms, or slowing the course of the disease by using immunosuppressant drugs such as corticosteroids or anti-TNF antibodies [231] (Table 5). Although most of the novel approaches for RA treatment are focused on the targeted delivery of immunosuppressant drugs or tissue regeneration, antigen-specific approaches are also being explored as a promising treatment at the onset of the disease through the downregulation of the underlying autoimmune processes, although the number is still limited [19,282,283]. Self-antigens, such as collagen derived peptides, were found to be RA triggers in different animal models [231], and mucosal administration of collagen peptides were found to ameliorate the progression of the disease in patients [284].…”
Section: The Potential Of Nanotechnology For Immunomodulation Of Amentioning
confidence: 99%
“…Moreover, liposomes were also explored in antigen-specific therapy for RA by Capini et al . In a methylated BSA-induced arthritis model, they showed that, after subcutaneous administration of methylated BSA and lipophilic NF-κβ inhibitors (Bay11-7082, curcumin, or quercetin) co-encapsulated in liposomes, all of the combined formulations diminished the score of disease symptoms, compared with untreated mice [283]. …”
Section: The Potential Of Nanotechnology For Immunomodulation Of Amentioning
confidence: 99%